2016
DOI: 10.1038/cddis.2016.321
|View full text |Cite
|
Sign up to set email alerts
|

The prosurvival protein BAG3: a new participant in vascular homeostasis

Abstract: Bcl2-associated athanogene 3 (BAG3), is constitutively expressed in a few normal cell types, including myocytes, peripheral nerves and in the brain, and is also expressed in certain tumors. To date, the main studies about the role of BAG3 are focused on its pro-survival effect in tumors through various mechanisms that vary according to cellular type. Recently, elevated concentrations of a soluble form of BAG3 were described in patients affected by advanced stage of heart failure (HF), identifying BAG3 as a pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Autophagy, on the other hand, is an adaptive response to environmental stresses including nutrient starvation due to tissue destruction or blood shortage, and it seems to be also required for the development of vascular ECs [80]. Downregulation of BAG3 could represent an increase in apoptosis but reduced autophagy [79,81], mainly in the CACtreated mice, although further studies should confirm such hypothesis. Overall, protein changes (upregulation and downregulation) taking place in ischemic non-treated mice indicated an upregulation of apoptosis and necrosis (according to the IPA functional Table 3 Classification of differentially expressed proteins in CAC-treated mice (SE) and non-treated mice (SC) vs shams (SH) on days 2 and 4 after femoral ligation.…”
Section: Discussionmentioning
confidence: 97%
“…Autophagy, on the other hand, is an adaptive response to environmental stresses including nutrient starvation due to tissue destruction or blood shortage, and it seems to be also required for the development of vascular ECs [80]. Downregulation of BAG3 could represent an increase in apoptosis but reduced autophagy [79,81], mainly in the CACtreated mice, although further studies should confirm such hypothesis. Overall, protein changes (upregulation and downregulation) taking place in ischemic non-treated mice indicated an upregulation of apoptosis and necrosis (according to the IPA functional Table 3 Classification of differentially expressed proteins in CAC-treated mice (SE) and non-treated mice (SC) vs shams (SH) on days 2 and 4 after femoral ligation.…”
Section: Discussionmentioning
confidence: 97%
“…CHAT (10q11.23, 136 kb downstream of rs4253197) encodes an enzyme that catalyzes the biosynthesis of the neurotransmitter acetylcholine, and binge ethanol in adolescents was reported to decrease CHAT expression[ 63 ]. BAG3 (10q26.11, 183 Kb downstream of rs201383951) was also suggested to contribute to alcohol-induced neurodegenerations[ 64 ]. A mouse study suggested that BAG3 exerts a vaso-relaxing effect through the activation of the PI3K/Akt/eNOS signaling pathway, and may influence BP regulation[ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…BAG3 (10q26.11, 183 Kb downstream of rs201383951) was also suggested to contribute to alcohol-induced neurodegenerations[ 64 ]. A mouse study suggested that BAG3 exerts a vaso-relaxing effect through the activation of the PI3K/Akt/eNOS signaling pathway, and may influence BP regulation[ 64 ]. A GWAS identified association of BAG3 with dilated cardiomyopathy[ 65 ], and suggestive association with alcohol dependence[ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…BAG3 protein is an anti-apoptotic protein involved in many other cellular processes, including cell cycle regulation, cell survival, proliferation, adhesion, migration, autophagy and EMT [ 5 , 7 , 10 , 16 , 22 , 28 ]. Some studies have shown that BAG3 can regulate these processes via the K-ras [ 29 ], EGFR [ 30 ] or AMPK/PI3K [ 31 ] signaling pathways. Studies have found that BAG3, a member of the co-chaperone family, contains the BAG domain, which can interact with the ATPase domain of heat shock protein 70 to regulate the HSP70 pathway [ 32 34 ].…”
Section: Discussionmentioning
confidence: 99%